Virtual instrumentation for a mini plant growth chamber / Zaira Hasnida Mohamed Rashid - Mohamed Rashid, Zaira Hasnida (2007)
In today's rapid development of technology, computer plays an important role in instrumentations including automation, process control, measurement and testing. One of the major developments resulting from the adoption of computer is the concept of virtual instrumentation. Virtual instrumentation is the software representation of traditional and new measurement instruments on a personal computer. With virtual instrumentation software, a custom instrument can be constructed. The virtual instrument will have the controls and displays that we want to see and use. It will accept the ranges we choose and will analyze measurement data in the manner we prescribe. This reports presents a user defined measurement system called virtual instrument. It is designed to display the output data of a mini plant growth chamber and to analyze the data. Controller is used to automate the final control element. The virtual instrumentation is written using Visual Basic 6.0. A set of real historical data was used to represents the output from a plant growth chamber. The work carried out here shows that virtual instrumentation can replace the real instrument.